Occupational tasks and changes in the wage structure - Sergio Firpo; Nicole M. Fortin; Thomas Lemieux (Institute for the Study of Labor (IZA), 2011)
This paper argues that changes in the returns to occupational tasks have contributed to changes in the wage distribution over the last three decades. Using Current Population Survey (CPS) data, we first show that the 1990s polarization of wages is explained by changes in wage setting between and within occupations, which are well captured by tasks measures linked to technological change and offshorability. Using a decomposition based on Firpo, Fortin, and Lemieux (2009), we find that technological change and deunionization played a central role in the 1980s and 1990s, while offshorability became an important factor from the 1990s onwards.
urn:nbn:de:101:1-201104133571
Keywords: J3; J5; 330; wage inequality; polarization; occupational tasks; offshoring; RIF-regressions; Lohnstruktur; Anforderungsprofil; Humankapital; Technischer Fortschritt; Offshoring; Schätzung; USA